A multiscale micromorphic model with strain rate relationship between MD simulations and macroscale experimental tests and dynamic heterogeneity for glassy polymers. (1st December 2020) - Park, Chanwook; Jung, Jiwon; Yun, Gun Jin
Abstract: This paper proposes a micromorphic simulation model with novel strain rate relationships between MD simulations and macroscale experiments at the ductile-brittle (DB) transition of glassy polymer and dynamic heterogeneity of deformation. Novelties of this paper are on the strain rate relationship between two different scale regions and investigations on the effects of molecular weight on the relationship. From molecular dynamics model having realistically entangled polymer networks and experiments, the strain rate relationships are derived and then realized through a two-scale multiscale continuum model based on the micromorphic theory. The investigation on the effects of molecular weights on the relationship yields that the relationship is maintained when the molecular weight is higher than the entanglement length. The relationship confirmed that the dynamic heterogeneity alleviates as the polymer enters into the plastic flow above the glass transition temperature and disappears above the melting temperature. These findings will be a basis for developing the constitutive relationship of glassy polymers through a multiscale approach that can incorporate the heterogeneous dynamics of molecules.